Bearing Capacity Characteristics of Sand Columns Stabilized with Recycled concrete and Glass Material in Soft Soils - Moamal Aqeel Abd-Alhusein; Dr. Ali Majid Al-Kinani (Genius Journals, 2023)
The objective of this study is to investigate the performance of reinforced compacted soil by the utilization of sand columns composed of recycled brick and cement. These columns are further stabilized with sodium silicate in order to enhance their structural integrity relative to the surrounding soil. The experimental program has been partitioned into three distinct phases with the objective of fabricating columns. The initial step involves the selection of the standard mixing proportions for each material and sodium silicate, considering three different weight percentages of liquid sodium silicate (10%, 15%, and 20%). The second approach involves enhancing the structural integrity of the brick and cement materials through the incorporation of sand at varying weight proportions (10%, 20%, 40%, and 60%). Samples were subjected to a laboratory test to determine their unconfined compressive strength (UCS). The experimental findings revealed that the cohesiveness of sand was significantly increased when 20% of cement and 20% of sodium silicate were added to the cement-sand combination. In the context of the bricks-sand mixture, it was observed that the optimal composition consisted of a 20% proportion of bricks and a 20% proportion of sodium silicate. The final phase of the study involved the utilization of a laboratory model to assess the efficacy of each mixture when applied to sand columns. During this phase of the laboratory experiments, the model test was conducted on three separate occasions. Initially, the earth was strengthened through the implementation of a solitary column. Furthermore, on the subsequent occasion, the structure was further strengthened with the addition of two additional columns. In the third instance, there were four columns present. The findings indicated that the enhancement ratio of the soil, which was reinforced with sand-cement columns and stabilized using sodium silicate, exhibited a 163% increase for a single column, a 256% increase for two columns, and a 358% increase for four columns. The sand-bricks column experiment yielded the following results: 46% for a single column, 144% for two columns, and 261% for four columns
Keywords: Sand column; sodium silicate; recycle concrete; glass